Engagement and metaphysical dissatisfaction modality and value - Stroud, Barry (New York ; Oxford : Oxford University Press, 2011)
We all have beliefs to the effect that if a certain thing were to happen a certain other thing would happen. We also believe that some things simply must be so, with no possibility of having been otherwise. Barry Stroud argues that some beliefs of each of these kinds are indispensable to our having any conception of a world at all.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Metaphysics; Causation; Necessity (Philosophy); Value